Effects of Parametric Uncertainty and Technological Change on Input-Output Models - III, Clark W. Bullard; Sebald, Anthony V. (The Review of Economics and Statistics, 1977)
Clark W. Bullard III, Anthony V. Sebald, Effects of Parametric Uncertainty and Technological Change on Input-Output Models, The Review of Economics and Statistics, Vol. 59, No. 1 (Feb., 1977), pp. 75-81